IMPLEMENTATION EFFECT KITAB AL 'ARABIYAH LILNASYIIN VOLUME 1 AND MOTIVATION TO LEARN ARABIC LANGUAGE ON LEARNING ACHIEVEMENT OF STUDENTS IN CLASS X AT SMAS COKROAMINOTO TAMALANREA - Kusrianty, Kusrianty (Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract: This article aims to discuss the influence of the application of kita<b al 'arabiyah lilna<syii<n vol 1 and motivation to learn Arabic on the learning achievement of class X students at SMA Cokroaminoto Tamalanrea , the research method used is quantitative research using exp method In fact , the data collection method is by observing interviews, questionnaires, and documentation. The results of the study show that the application of Kita < b al-'Arabiyah Lilna < sy ii < n Volume 1 at SMAS Cokroaminoto Tamalanrea is in the Moderate and significant category with a percentage of 54%. This illustrates that the Application of Kita < b al-'Arabiyah Lilna < sy ii < n Volume 1 at SMAS Cokroaminoto Tamalanrea has gone well. Motivation to learn Arabic for students at SMAS Cokroaminoto Tamalanrea is in the Medium category with a percentage of 60%, meaning that motivation Learn Arabic for Students at SMAS Cokroaminoto Tamalanrea very well implemented.